Menakar moralitas elit politik melalui kontrak politik - Nasiwan Nasiwan (Jurnal Civics: Media Kajian Kewarganegaraan, 2004)
Before the General Election to choose the legislative members, that is held on April 5, 2005 and President General Election, that is held on June 5 and September 20, 2004, there was a political phenomenon, which then popularly said "a political contract. " The political contract was initiated by some elements of 'the civil society', which were the important components of the political power of pro-reform community. Looking at the cultural side, the existence of the political contract in the development of Indonesian politics implied that there was a change in cognitive, affective and evaluation  orientation of some of Indonesian people in their attitudes and political habits to be more rational.  The emergence of the more-rational political orientation was also pushed by the previous political experience of ''being betrayed by the political elite ', just like in 1999 General Election at the reform era. The chance also rose after the changes in the system of General Election that introduced the district and proportional system, and the direct president election that rose up the important of people's vote and aspiration. The changes had pushed the political elites to approach the people, fit themselves with the people's rhythm and dynamism, including the aspiration for political transparency and political accountability by willing to sign the political contract.